Homeschool background, time use and academic performance at a private religious college. Issue 3 (4th May 2019) - Bennett, Daniel L.; Edwards, Elyssa; Ngai, Courtney
Abstract: We study the effects of homeschool background and time use on academic performance among students at Patrick Henry College, a private religious institution with a 63-credit core classical liberal arts curriculum. Using ordinary least squares regression analysis, we examine four research questions: (1) Does time use influence academic performance? (2) Do homeschooled students perform differently than traditionally schooled students? (3) Does parental education moderate the impact of homeschooling on academic performance? (4) Does homeschooling moderate the impact of ACT scores on academic performance?